Microcapsule Application of Kecombrang Flower Extract: Effects of Concentration, Types of Fraction, pH of Medium, and NaCl on Microbiological Properties of Minced Beef - Naufalin, R; Herastuti, SR (ANIMAL PRODUCTION, 2013)
Abstract. Kecombrang (Nicolaia speciosa Horan), in addition to  flavor and medicinal uses, it has potential as antimicrobial substances. The bioactive components in kecombrang are alkaloids, flavonoids, polyphenols, steroids, saponin and atsiri oils. This research was aimed to study the effectiveness of microcapsule from flower extract of kecombrang added to minced beef; the effects of pH interaction and NaCl addition on antimicrobial activity. The research used a Randomized Completely Block Design factorial pattern with 24 treatment combinations and 2 replications. The tested factors were type and microcapsule concentration ( control, ethanol extract  5%, etanol extract 10%, ethyl acetate extract 5% and ethyl acetate extract 10%), pH medium (pH 4 dan pH 7), and NaCl concentration (0% 2,5% and 5%). The results showed the microcapsule of flower extract of kecombrang that have antimicrobial activities in boiled minced beef was etyl acetate extract of 10% concentration under pH 4 and 5% NaCl . Keywords : Microcapsule, kecombrang, natural preservative, minced beef. Abstrak. Kecombrang (Nicolaia speciosa Horan) selain sebagai pemberi cita rasa dan berkhasiat obat, juga berpotensi sebagai antimikroba. Komponen bioaktif yang terdapat dalam kecombrang yaitu alkaloid, flavonoid, polifenol, steroid, saponin dan minyak atsiri. Penelitian ini bertujuan untuk mengetahui efektivitas mikrokapsul dari ekstrak bunga kecombrang yang ditambahkan pada daging sapi giling, pengaruh perlakuan pH dan penambahan NaCl terhadap potensi antimikroba.  Penelitian ini menggunakan Rancangan Acak Kelompok (RAK) factorial dengan  24 kombinasi perlakuan dan 2 kali ulangan.  Faktor yang diteliti adalah jenis dan konsentrasi mikrokapsul yaitu ( kontrol, ekstrak etanol  5%, ekstrak etanol 10%, ekstrak  etil asetat 5% dan  ekstrak etil asetat 10%), pH medium (pH 4 dan pH 7), dan konsentrasi NaCl (0% 2,5% dan 5%).  Hasil penelitian menunjukkan bahwa mikrokapsul ekstrak bunga kecombrang yang dapat berfungsi sebagai antimikroba pada daging giling rebus adalah ekstrak etil asetat  pada konsentrasi 10% dengan pengaturan pada pH  4 dan pada konsentrasi NaCl 5 %. Kata kunci :  Mikrokapsul, kecombrang, pengawet alami,  daging giling.R Naufalin and SR Herastuti/Animal Production 15(1):8-14, January 2013